Effects of low-pressure igneous processes and subduction on Fe3+/ΣFe and redox state of mantle eclogites from Lace (Kaapvaal craton) - Aulbach, S.; Woodland, A.; Vasilyev, Prokopiy; Galvez, M.; Viljoen, K. (Elsevier BV, 2017)
© 2017 Elsevier B.V. Reconstructing the redox state of the mantle is critical in discussing the evolution of atmospheric composition through time. Kimberlite-borne mantle eclogite xenoliths, commonly interpreted as representing former oceanic crust, may record the chemical and physical state of Archaean and Proterozoic convecting mantle sources that generated their magmatic protoliths. However, their message is generally obscured by a range of primary (igneous differentiation) and secondary processes (seawater alteration, metamorphism, metasomatism). Here, we report the Fe3+/SFe ratio and d18O in garnet from in a suite of well-characterised mantle eclogite and pyroxenite xenoliths hosted in the Lace kimberlite (Kaapvaal craton), which originated as ca. 3 Ga-old ocean floor. Fe3+/SFe in garnet (0.01 to 0.063, median 0.02; n=16) shows a negative correlation with jadeite content in clinopyroxene, suggesting increased partitioning of Fe3+into clinopyroxene in the presence of monovalent cations with which it can form coupled substitutions. Jadeite-corrected Fe3+/SFe in garnet shows a broad negative trend with Eu?, consistent with incompatible behaviour of Fe3+during olivine-plagioclase accumulation in the protoliths. This trend is partially obscured by increasing Fe3+partitioning into garnet along a conductive cratonic geotherm. In contrast, NMORB-normalised Nd/Yb – a proxy of partial melt loss from subducting oceanic crust (<1) and metasomatism by LREE-enriched liquids (>1) – shows no obvious correlation with Fe3+/SFe, nor does garnet d18OVSMOW(5.14 to 6.21‰) point to significant seawater alteration. Median bulk-rock Fe3+/SFe is roughly estimated at 0.025. This observation agrees with V/Sc systematics, which collectively point to a reduced Archaean convecting mantle source to the igneous protoliths of these eclogites compared to the modern MORB source. Oxygen fugacites (fO2) relative to the fayalite–magnetite–quartz buffer (FMQ) range from ?log?fO2= FMQ-1.3 to FMQ-4.6. At those reducing conditions, the solubility of carbon in the fluids released by dehydration is higher than in fluids closer to FMQ. The implication is that Archean processes of C transport and deposition would have differed from those known in modern-style subduction zones, and diamond would have formed from methane-rich fluids. In addition, such reducing material could drive redox melting or freezing upon deep recycling and migration of CH4-bearing fluids into the ambient mantle.